Copper fabric improves the metabolic profile of obese mice: Potential role of the gut microbiota. Issue 5 (30th August 2022) - Song, Erfei; Vu, Vivian; Varin, Thibault V.; Botta, Amy; Marette, André; Sweeney, Gary
Abstract: Copper and copper alloys have antimicrobial activity through the rapid contact killing of viruses, bacteria and yeasts on their surface. Dysregulation of host microbiota can contribute to the pathogenesis of inflammatory diseases such as obesity, diabetes and cardiovascular disease. Anecdotal evidence noted improved overall well‐being in individuals sleeping on copper‐containing fabric bedding. We hypothesized that the beneficial effect of copper‐infused fabric bedding on cardiometabolic health is linked to changes in gut microbiota composition. This study utilized a mouse model of diet‐induced obesity to assess the beneficial effects of copper‐infused fabric bedding on metabolic health. Body composition, inflammatory markers, metabolic and cardiovascular status and changes in the faecal microbiota composition were evaluated for up to 2 months in mice fed with a normal chow diet or high fat high cholesterol diet in the presence of bedding made with and without copper‐infused fabric. Results showed that mice subjected to diet‐induced obesity and housed in cages with copper‐infused fabric liner displayed less body weight gain than mice in cages with control fabric. Mice housed with copper‐infused fabric also displayed improved glucose tolerance and reduced inflammation biomarker lipocalin‐2. We also observed a beneficial shift in gut bacterial composition of obese mice housed with copper fabric bedding. Taken in conjunction, our study provides direct animal‐based evidence supporting the beneficial effects of copper fabric on metabolic health.